2007
DOI: 10.1080/17453670710013924
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ACL deficiency on mediolateral translation and varus–valgus rotation

Abstract: Background The anterior cruciate ligament (ACL) constrains the anterior translation and axial rotation of the tibia. However, the effect of ACL injury on the mediolateral translation and varus-valgus rotation of the tibia is unknown. Because of the oblique orientation of the ACL, we hypothesized that ACL deficiency alters mediolateral translation and varus-valgus rotation.Methods The kinematics of 9 cadavers from full extension to 90° of flexion under various loading conditions were measured before and after A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 22 publications
8
71
0
Order By: Relevance
“…Previous studies about knee kinematics, both in-vivo (DeFrate et al, , 2006Komistek et al, 2003;Lafortune et al, 1992;Lu et al, 2008;Mahfouz et al, 2004;Patel et al, 2004;Seisler and Sheehan, 2007;Shefelbine et al, 2006;Shelburne et al, 2005;Williams and Logan, 2004) and in-vitro (Belvedere et al, 2007a;Blaha et al, 2003;Churchill et al, 1998;Iwaki et al, 2000;Li et al, 2004Li et al, , 2007Most et al, 2004;Papaioannou et al, 2008;Pinskerova et al, 2004;Walker and Haider, 2003;Wilson et al, 2000), have dealt with axial rotation, articular contact point locations, anteroposterior sliding and femoral posterior rolling by different methodological approaches and measuring devices (Amiri et al, 2006(Amiri et al, , 2007Bull and Amis, 1998;Freeman and Pinskerova, 2005;Moglo and Shirazi-Adl, 2005;Ramsey and Wretenberg, 1999). These did not analyze in depth the contemporary presence of all three translational components.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies about knee kinematics, both in-vivo (DeFrate et al, , 2006Komistek et al, 2003;Lafortune et al, 1992;Lu et al, 2008;Mahfouz et al, 2004;Patel et al, 2004;Seisler and Sheehan, 2007;Shefelbine et al, 2006;Shelburne et al, 2005;Williams and Logan, 2004) and in-vitro (Belvedere et al, 2007a;Blaha et al, 2003;Churchill et al, 1998;Iwaki et al, 2000;Li et al, 2004Li et al, , 2007Most et al, 2004;Papaioannou et al, 2008;Pinskerova et al, 2004;Walker and Haider, 2003;Wilson et al, 2000), have dealt with axial rotation, articular contact point locations, anteroposterior sliding and femoral posterior rolling by different methodological approaches and measuring devices (Amiri et al, 2006(Amiri et al, , 2007Bull and Amis, 1998;Freeman and Pinskerova, 2005;Moglo and Shirazi-Adl, 2005;Ramsey and Wretenberg, 1999). These did not analyze in depth the contemporary presence of all three translational components.…”
Section: Introductionmentioning
confidence: 99%
“…With use of the robotic testing system, we measured the kinematics in nine cadaver tibiofemoral joints, from full extension to 90°of flexion both before and after anterior cruciate ligament resection, and found that anterior cruciate ligament deficiency not only altered anterior translation and axial rotation of the tibia (findings that have been documented extensively in the in vitro and in vivo literature [31][32][33][34][35][36] ) but also increased the medial translation of the tibia 37 . Our in vivo dual fluoroscopic imaging analysis of the tibiofemoral kinematics in ten patients with acute anterior cruciate ligament deficiency revealed analogous findings: an increased anterior translation (approximately 3 mm, Fig.…”
Section: Disturbed Tibiofemoral Joint Kinematicsmentioning
confidence: 99%
“…As the centre of the tibia in Figure 1(b) is travelling along an arc, it should come to rest slightly more medially than in Figure 1(a). Results of studies in vivo (DeFrate et al, 2006) and in vitro (Li et al, 2007;Seon et al, 2010;Van de Velde et al, 2009) show that transection or rupture of the ACL increases medial tibial translation. So the ACL-deficient knee appears to either combine anterior translation, internal rotation and medial translation, or the more parsimonious alternative of internally rotating about a medially shifted axis.…”
Section: Combined Anterior Translation/internal Rotationmentioning
confidence: 99%